Minimum capital requirements for market risk: An overview and critical analysis of the standardized approaches under Basel III - Stefan Best (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifin), 2021)
Im Januar 2019 veröffentlichte der Baseler Ausschuss für Bankenaufsicht eine revidierte Fassung der Mindestanforderungen an Eigenkapital für Marktrisiken, die am 01.01.2023 in Kraft treten wird. Diese Arbeit beschäftigt sich mit dem auf Sensitivitäten basierenden Standardansatz und dem Vereinfachten Standardansatz. Neben der Darstellung und kritischen Analyse beider Ansätze wird untersucht, wie sich die Ansätze in ihren Auswirkungen auf die Eigenkapitalanforderungen unterscheiden. Zudem werden die Ergebnisse für Instrumente mit Ausfallrisiko mit denen des Standardansatzes des Bankbuchs verglichen. Insbesondere wird gezeigt, dass der auf Sensitivitäten basierende Standardansatz konzeptionelle und technische Schwachstellen aufweist. Er ist zudem unnötig kompliziert und läuft so der vom Baseler Ausschuss selbst formulierten Forderung nach mehr Transparenz und Vereinfachung zuwider. – – In January 2019, the Basel Committee on Banking Supervision published a revised version of the minimum capital requirements for market risk, which will take effect on January 1, 2023. This paper focuses on the sensitivity-based standardized approach and the simplified standardized approach. In addition to presenting and critically analyzing both approaches, the paper examines how the approaches differ in their impact on capital requirements. Moreover, the results for instruments with default risk are compared with those of the standardized approach for the banking book. In particular, it is shown that the sensitivity-based standardized approach has conceptual and technical weaknesses. It is also unnecessarily complicated and thus runs counter to the Basel Committee's own call for greater transparency and simplification.
Keywords: G21; G28; 330; Basel III; Standardized Approach; Market Risk; Minimum capital requirements